Pemanfaan Neurosains dalam Desain Pengembangan Kurikulum Bahasa Arab - Fauzi, Muhammad Ilfan (Institut Agama Islam Negeri Curup, 2020)
This paper discusses the contribution of neuroscience in the development of the Arabic language curriculum of the modern era with the development of a very strategic and practical reconstruction. One of them is the emergence of integration between nation, brain based learning, and character building using a neuroscience approach. The basic point of this study is the right brain functional statement as the basic for developing the Arabic language curriculum. The purpose of this paper is to provide an understanding that the learning process of Arabic can be integrated with the neuroscience approach. This type of research used library research with content analysis in the form of descriptive analysis using primary sources in the form of bibliographies and scientific journal articles. The results showed that the application of neuroscience can be implemented in the formulation of Arabic curriculum development with a series; 1) optimization of the right and left brain nerve system; 2) integrating the role of the brain into the educational and psychological basis of cognitive aspects (Arabic substance), psychomotor (mastery of Arabic language skills), and affective (attitudes, values, and characters) into Arabic learning; 3) interconnecting these three aspecs into the nature of the objectives, methods, strategies of learning Arabic. On this basis, neuroscience can be implicated in the standard development of Arabic learning curriculum in the modern era.